ANALISIS PERTUMBUHAN SIMPANAN SUKARELA ANGGOTA DI CU. KHATULISTIWA BAKTI KP. KOTA BARU TAHUN 2013-2017 - Liberta, Hellena; Ulfah, Maria; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThe title of this thesis is "Growth Analysis of Voluntary Member Savings at CU. Khatulistiwa Bakti KP. Kota Baru in the 2013-2017 Period ". This study aimed to determine the Voluntary Savings Growth Analysis of Members at CU. Khatulistiwa Bakti Pontianak KP. Kota Baru in the period 2013-2017. The form of research used was survey studies. With the manager of the credit union CU. Khatulistiwa Bakti as a resource person and as a respondent. The method used was descriptive method with the aim of explaining objectively the Growth Analysis of Voluntary Member Savings at CU. Khatulistiwa Bakti KP. Kota Baru in the period 2013-2017. Data collection tools are direct communication techniques, documentary study techniques, interviews and documentation. While the data processing was qualitative descriptive analysis. The results of this study stated that the Voluntary Savings Growth Analysis of Members at CU. Khatulistiwa Bakti Pontianak KP. Kota Baru Dalam Period 2013-2017 is positive, meaning that the growth of voluntary deposits of members is always aggressive or always experiencing growth and development both seen from the number of members or members of deposits in each year, so there are no problems in growth or development.Â Keywords: Growth analysis, voluntary deposits, members